Analysis of Stunting Events in Children at Puskesmas Konda, South Konawe District Southeast Sulawesi Province : Analisis Kejadian Stunting pada Balita Di Puskesmas Konda, Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara - Fitriana, Estri Seta; Dinengsih, Sri; Siauta, Jenny Anna (Jurnal Kebidanan Midwiferia, 2021)
The incidence of stunting, known as stunting, is one of the nutritional problems experienced by toddlers in the world today. In 2017 22.2% or around 150.8 million children under five in the world were stunted. Konawe Selatan District, the average stunting rate per August 2020 is 18 percent and there are 5% (125) of the total 2,550 children with disabilities at the Konda Health Center experiencing stunting. To determine the analysis of the incidence of stunting in children under five and to determine the relationship between knowledge, family income, diet, exclusive breastfeeding and low birth weight on the incidence of stunting. This study is a case control study. The sample is 116 mothers who have children aged 2-5 years with purpose sampling. The instruments used were height gauges, MCH books and questionnaire sheets. The validity test adopted Prakhasita's (2018) research questionnaire. Data were analyzed using the Chi Square test. Mothers who have toddlers who have good knowledge 43 (37.1%) mothers who have toddlers, family income is according to 50 (43.1%) mothers who have toddlers, proper dietary patterns 36 (31%) mothers who have toddlers , Exclusive breastfeeding 45 (38.8%) mothers who have toddlers, LBW 30 (25.9%) mothers who have toddlers. There is a relationship between knowledge, family income, diet, exclusive breastfeeding and low birth weight to the incidence of stunting in the Konda District Health Center. South Konawe 2020. There is a significant relationship between knowledge of the incidence of stunting and the OR = 67.529. Puskesmas are expected to